Semi-organic crystal N2H4Zn(HC3N3O3) and its preparation method and application
By developing semi-organic crystal N2H4Zn (HC3N3O3) and preparing the material by hydrothermal reaction method, the problems of difficulty in synthesis and insufficient performance of existing nonlinear optical materials are solved, and the combination of strong second harmonics and ultra-long room temperature phosphorescence life is achieved, which significantly improves the optical performance of the material.
Patent Information
- Application Number
- CN202411078891.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-07
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-08-07
AI Technical Summary
Existing nonlinear optical materials have problems such as difficulty in synthesis, poor optical quality, and slow electro-optical response time. Research on combining nonlinear effects with fluorescence and phosphorescence properties of multifunctional photoelectric materials is relatively scarce.
A semi-organic crystal N2H4Zn (HC3N3O3) was developed, and the material was prepared by hydrothermal reaction method. The coordinated combination of Zn2+ coordination trend, HC3N3O32-construction unit and N2H4 ligand was used to form an asymmetric structure, promote exciton transfer and inter-system crossing, and improve the second harmonic and phosphorescence properties.
The material exhibits strong second harmonics, ultra-long room temperature phosphorescence lifetime, high thermal stability and strong water resistance, and presents a tunable blue and green afterglow visible to the naked eye within 1.2 seconds. The SHG intensity exceeds 13 times that of KDP and the RTP life reaches 448ms.
Smart Images

Figure CN119039326B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of nonlinear optical (NLO) materials, and relates to semi-organic crystal N2H4Zn (HC3N3O3) and a preparation method and application thereof. Background Art
[0002] Nonlinear optical materials refer to materials whose optical properties depend on the intensity of incident light. For example, the refractive index, absorption coefficient, and light scattering of the material will change with the intensity of the light field, electric field, and strain field. These materials can achieve light wave frequency conversion, which makes it possible to realize all-optical computing, switching, and long-distance communication, and has broad application prospects.
[0003] Traditional nonlinear optical materials are mainly inorganic crystals, which have problems such as difficult synthesis, poor optical quality, and slow electro-optical response time, which seriously restrict the synthesis and application of materials. Semi-organic materials that combine the advantages of organic and inorganic parts have great application potential and have become a research hotspot in the field of nonlinearity. However, reports on multifunctional optoelectronic materials that combine nonlinear effects with the fluorescence, phosphorescence and other properties of traditional organic materials are still very rare. Summary of the invention
[0004] The present invention has discovered a semi-organic crystal N2H4Zn (HC3N3O3) which has strong second harmonic, ultra-long room temperature phosphorescence lifetime, high thermal stability and strong water resistance. In addition, the semi-organic crystal shows tunable multi-color room temperature phosphorescence accompanied by a long-lasting afterglow visible to the naked eye of up to 1.2 seconds.
[0005] The technical solution provided by the present invention is as follows:
[0006] A first aspect of the present invention provides a semi-organic crystalline material, wherein the chemical formula of the semi-organic crystal is N2H4Zn(HC3N3O3).
[0007] In some embodiments of the present invention, the semi-organic crystal belongs to the monoclinic system and has a space group of Cc.
[0008] In some embodiments of the present invention, the unit cell parameters of the semi-organic crystal are: α=90°,β=113.333(2)°,γ=90°,unit cell volume
[0009] In some embodiments of the present invention, the semi-organic crystal has a tetrahedral structure centered on Zn when viewed from the c-axis direction.
[0010] In some embodiments of the present invention, the semi-organic crystal has two [Zn(N2H4)] 2+∞) infinite chain and two [Zn 2+ (HC3NH3O3) 2- ]∞ infinite chain, viewed from the c-axis direction, two [Zn(N2H4)] 2+ ∞) infinite chain and two [Zn 2+ (HC3NH3O3) 2- ]∞Infinite chains are connected to form a diamond-like topological three-dimensional structure.
[0011] The second aspect of the present invention provides a method for preparing a semi-organic crystalline material, wherein CH6N4·HNO3, ZnBr2 and C3H3N3O3 are subjected to a hydrothermal reaction to obtain the semi-organic crystalline material.
[0012] In some embodiments of the present invention, CH6N4·HNO3, ZnBr2 and C3H3N3O3 are subjected to a hydrothermal reaction to obtain a semi-organic crystalline material, comprising:
[0013] The semi-organic crystalline material is obtained by keeping CH6N4·HNO3, ZnBr2 and C3H3N3O3 in a molar ratio of 1:1:1 in water at 120-160°C for 2 to 7 days and then cooling to room temperature within 1 to 5 days.
[0014] The third aspect of the present invention provides the use of the above-mentioned semi-organic crystalline material in any field of optical computing, optical switching, long-distance communication, information encryption and anti-counterfeiting, biological imaging, lighting, and long afterglow devices.
[0015] A fourth aspect of the present invention provides a nonlinear optical device, which is constructed using the above-mentioned semi-organic crystalline material.
[0016] A fifth aspect of the present invention provides a nonlinear optical device, comprising the above-mentioned nonlinear optical device.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] Compared with existing metal cyanurates, the semi-organic crystal N2H4Zn (HC3N3O3) provided by the present invention has the strongest second harmonic, which is 13 times that of KDP (potassium dihydrogen phosphate); and has an abnormally long room-temperature phosphorescence lifetime (448ms); the material exhibits visible and tunable blue and green afterglow for up to 1.2 seconds. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0020] Figure 1 :(a) Highly diamond-like topological structure of [Zn(HC3N3O3)2(N2H4)]2]. (b) [Zn 2+ (HC3N3O3) 2- ] ∞ Infinite chain. (c) Infinite chain. (d) Highly polarized [Zn(HC3N3O3)2(N2H4)2] tetrahedron. (e) N2H4, HC3N3O3 and Zn that make up [Zn(HC3N3O3)2(N2H4)2] tetrahedron 2+ Three structural units. (f) Spatial arrangement of polarized [Zn(HC3N3O3)2(N2H4)2] groups (the red dashed box indicates [Zn 2+ (HC3NH3O3) 2- ] ∞ Infinite chain, the orange dashed box represents [Zn(N2H4)] 2+ ∞ Infinite chain).
[0021] Figure 2 Optical properties of N2H4Zn(HC3N3O3): (a) UV-vis diffuse reflectance spectrum, inset: experimental band gap calculated using Kubelka-Munk function. (b) Calculated birefringence. (c) Particle size-dependent SHG intensity under 1064 nm laser irradiation. (d) SHG signal intensity for samples with a particle size range of 180-280 μm.
[0022] Figure 3 :Water resistance test of N2H4Zn(HC3N3O3) crystal (when irradiated by 1064nm laser, the crystal emits 532nm green light).
[0023] Figure 4 : Phosphorescence spectrum of N2H4Zn(HC3N3O3). Emission spectrum at (a) 310nm; (b) 365nm; (c) 290-410nm. (d) CIE chromaticity spectrum at excitation wavelengths from 310 to 365nm.
[0024] Figure 5 : Decay curves of N2H4Zn(HC3N3O3) at (a) 310nm and (b) 365nm. (c) Comparison of phosphorescence lifetimes of 11 compounds: [Zn4(HEDP)2(TIMB)]·H2O(1), (Ph3S)2ZnCl4(2), (Ph3S)2MnCl4(3), [NH3Me]·[Zn2(HEDP)(TPA) 0.5(H2O)2]·2H2O(4), [Zn5(BIPA)4MIM(OH)2(H2O)2](5), [Zn3(BIPA)2(MIM)3(OH)2]·2H2O(6), Zn(HCOO)2(4,4'-bipy)(7), ZnCl2·R-2-MP(8), ZnCl2·S-2-MP(9), Na2Zn2(C9H3O6)2(H2O)8·3H2O(10) and the title compound (11). (d) Photographs of N2H4Zn(HC3N3O3) before and after removal of 310nm and 365nm UV light.
[0025] Figure 6 :Electron distribution curves of N2H4Zn(HC3N3O3) (a) VBM and (c) CBM. N2H4Zn(HC3N3O3) crystal d 11 SHG weight factor analysis of components (b) and (d). DETAILED DESCRIPTION
[0026] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] For simplicity, only some numerical ranges are explicitly disclosed herein. However, any lower limit can be combined with any upper limit to form an unambiguous range; and any lower limit can be combined with other lower limits to form an unambiguous range. Similarly, any upper limit can be combined with any other upper limit to form an unambiguous range. In addition, although not explicitly stated, each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unambiguous range.
[0028] It should be noted that, in the description of this article, unless otherwise specified, "above", "below" are inclusive numbers, and the meaning of "multiple" in "one or more" is two or more. Relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of more restrictions, the elements defined by the sentence "including one..." do not exclude the existence of other identical elements in the process, method, article or equipment including the elements.
[0029] In the description of this specification, the description with reference to the terms "any embodiment / method", "one embodiment / method", "some embodiments / methods", "example", "specific example" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment / method or example are included in at least one embodiment / method or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment / method or example. Moreover, the specific features, structures, materials or characteristics described may be combined in a suitable manner in any one or more embodiments / methods or examples. In addition, those skilled in the art may combine and combine the different embodiments / methods or examples described in this specification and the features of the different embodiments / methods or examples, unless they are contradictory.
[0030] The above summary of the invention of the present invention is not intended to describe each disclosed embodiment or each implementation in the present invention. The following description more specifically illustrates exemplary embodiments. These embodiments can be used in various combinations. In each example, the enumeration is only used as a representative group and should not be interpreted as exhaustive.
[0031] Semi-organic crystalline materials
[0032] As described in the background, semi-organic nonlinear crystals are a promising class of materials that combine the processability and tunability of organic components with the structural stability of inorganic components. In existing semi-organic crystalline materials, strong second harmonic generation (SHG) and ultra-long room temperature phosphorescence (RTP) cannot be achieved simultaneously.
[0033] The present invention provides a semi-organic crystalline material with strong second harmonic generation and ultra-long room temperature phosphorescence, the chemical formula of which is N2H4Zn(HC3N3O3). In the cyanurate system, the SHG intensity of the semi-organic crystalline material is the highest (13×KDP), and the RTP lifetime can reach 448ms, accompanied by a 1.2s long-lasting afterglow visible to the naked eye, which exceeds many current metal-organic complexes.
[0034] The design principle of the semi-organic crystalline material N2H4Zn (HC3N3O3) provided by the present invention is: using Zn 2+ SHG activity of coordination trend, HC3N3O3 2- The synergistic combination of building blocks and unique neutral N2H4 ligands not only forms a non-centrosymmetric (NCS) structure that is favorable for SHG activity, but also promotes efficient exciton transfer and intersystem crossing (ISC), which is critical for RTP. The SHG of N2H4Zn(HC3N3O3) is the strongest among metal cyanurates to date, exceeding KDP by 13 times, and the RTP lifetime is 448ms, which is unusually long for metal complexes. In addition, the material exhibits visible and tunable blue and green afterglow for up to 1.2 seconds.
[0035] In some embodiments of the present invention, the semi-organic crystal belongs to the monoclinic system and has a space group of Cc.
[0036] In some embodiments of the present invention, the unit cell parameters of the semi-organic crystal are: α=90°,β=113.333(2)°,γ=90°,unit cell volume
[0037] In some embodiments of the present invention, the semi-organic crystal has a tetrahedral structure centered on Zn when viewed from the c-axis direction.
[0038] In some embodiments of the present invention, the semi-organic crystal has two [Zn(N2H4)] 2+ ∞] infinite chain and two [Zn 2+ (HC3NH3O3) 2- ]∞ infinite chain, viewed from the c-axis direction, two [Zn(N2H4)] 2+ ∞) infinite chain and two [Zn 2+ (HC3NH3O3) 2- ]∞Infinite chains are connected to form a diamond-like topological three-dimensional structure.
[0039] Preparation method
[0040] When preparing the semi-organic crystalline material N2H4Zn(HC3N3O3), the measured CH6N4·HNO3, ZnBr2 and C3H3N3O3 are subjected to hydrothermal reaction to successfully synthesize a crystalline material with a size of up to 5×2×1 mm. 3 The present invention verifies the purity of the N2H4Zn(HC3N3O3) bulk single crystal by powder X-ray diffraction (PXRD) data, which is very consistent with the simulation results of single crystal X-ray diffraction.
[0041] The preparation method of the semi-organic crystalline material provided by the present invention comprises: subjecting CH6N4·HNO3, ZnBr2 and C3H3N3O3 to a hydrothermal reaction to obtain the semi-organic crystalline material; more specifically, subjecting CH6N4·HNO3, ZnBr2 and C3H3N3O3 in a molar ratio of 1:1:1 to heat in water at 120-160°C for 2-7 days and cooling to room temperature within 1-5 days to obtain the semi-organic crystalline material. The water used is preferably deionized water, and the ratio of raw materials to water is such that 3 mL of deionized water is added for every 1 mmol of ZnBr2.
[0042] application
[0043] As mentioned above, the semi-organic crystalline material of the present invention has high SHG activity and an RTP lifetime of up to 448 ms, and exhibits tunable blue and green afterglow visible to the naked eye for up to 1.2 seconds. It can be used in any field of optical computing, optical switching, long-distance communication, information encryption and anti-counterfeiting, bio-imaging, lighting, and long afterglow devices.
[0044] Furthermore, by utilizing the high SHG activity of the semi-organic crystalline material, a nonlinear optical device is constructed using the semi-organic crystalline material, and the nonlinear optical device is applied to a nonlinear optical apparatus.
[0045] Example
[0046] The following are the raw materials used in the invention: aminoguanidine nitrate (CH6N4·HNO3, ≥99%), zinc bromide (ZnBr2, ≥99%), and cyanuric acid (C3H3N3O3, ≥99%). The present invention does not further purify all reagents, but uses them directly.
[0047] Example 1
[0048] The invention adopts a hydrothermal method to synthesize semi-organic crystal N2H4Zn (HC3N3O3), and the preparation method specifically comprises the following steps: a mixture of aminoguanidine nitrate (0.2742 g, 2.0 mmol), zinc bromide (0.4504 g, 2.0 mmol), cyanuric acid (0.2581 g, 2.0 mmol) and distilled water (3 mL) is sequentially placed in a 23 mL polytetrafluoroethylene lined autoclave. Then, the temperature is raised from room temperature to 150°C for 2 hours, maintained for 4 days, and slowly cooled to room temperature within 5 days. The semi-organic crystal N2H4Zn (HC3N3O3) is washed with anhydrous ethanol to obtain colorless block crystals.
[0049] Instrument and characterization description
[0050] 1. Single crystal X-ray diffraction
[0051] The XtaLAB Synergy R diffractometer (MoKα radiation, ) were collected for single crystal X-ray diffraction (XRD) data of the compound. Olex2 was used, the structure was solved using ShelXT, and the structure was refined using the intrinsic phase method and least squares minimization. The crystal information is summarized in Table 1.
[0052] 2. Powder X-ray Diffraction
[0053] Powder X-ray diffraction (P-XRD) data were recorded on an Advance diffractometer at 40 kV, 100 mA, and Cu Kα1 radiation (Bruker D8, radiation wave number ), the scanning speed was 10° / min, and the scanning angle range was 10-70°. The phase purity was determined by powder X-ray diffraction technique.
[0054] 3. Infrared spectroscopy
[0055] IR spectra were collected on a Nicolet iS5 Fourier transform infrared (FTIR) spectrometer at room temperature (measurement range 4000–400 cm -1 ). The sample and dry KBr were mixed and ground in a weight ratio of 1:100, and pressed into thin sheets for measurement.
[0056] 4. UV-Vis diffuse reflectance spectroscopy
[0057] UV-vis diffuse reflectance spectra were obtained at room temperature using a Varian Cary 5000 spectrophotometer (test range 200-800 nm). Spectrally pure barium sulfate was selected as a reference (100% reflectance) and the ground powder samples were coated on its surface for testing.
[0058] 5. Phosphorescence
[0059] Phosphorescence excitation spectra and luminescence emission decays were measured on a Hitachi F-4700 spectrophotometer.
[0060] 6. Thermal analysis
[0061] Thermogravimetric analysis (TGA) was performed using a Netzsch STA 449F5 analyzer. About 0.8 mg of sample was weighed and placed in a platinum crucible under nitrogen atmosphere at 10 K min -1 The rate of heating is from room temperature to 800°C.
[0062] 7. Second harmonic generation measurement
[0063] Second-order nonlinear optical measurements were performed on the powder samples at room temperature, and the SHG effect of the powder samples was measured using a modified Kurtz and Perry method using a Q-switched 1064nm Nd:YAG laser. Polycrystalline samples of the compound were sieved into different particle sizes (35-50, 50-74, 74-100, 100-154, 154-180 and 180-280μm) to investigate whether their SHG responses can be phase matched. A reference substance, KH2PO4 (KDP for short), was selected to compare the SHG efficiency of the samples to evaluate the second-order nonlinear optical effect of the measured samples.
[0064] 8. Birefringence measurement
[0065] The birefringence characteristics of N2H4Zn(HC3N3O3) obtained by polarizing microscopy at 589nm. The birefringence was calculated using the following formula:
[0066] R=Δn×d
[0067] R represents the optical path difference, Δn represents the birefringence, and d represents the thickness of the crystal.
[0068] 9. Calculation method
[0069] The calculation method of the present invention is based on the framework of density functional theory, and the electronic structure and optical properties of N2H4Zn (HC3N3O3) are calculated using the CASETEP module of Materials Research 8.0. In order to define the exchange correlation potential, the generalized gradient approximation of the PBE functional is used under GGA conditions to obtain a stable optimal structure. The battery structure is optimized using the BFGS algorithm, and the interaction between the valence electrons and the ionic solid is described using ultrasoft pseudopotentials. The valence electron states of C, N, O, H, and Zn are 2s 2 2p 2 , 2s 2 2p 3 , 2s 2 2p4 , 1s1 and 3p 6 3d 10 4s 2 The plane wave cutoff energy was set to 420 eV, and the Brillouin zone was numerically integrated using a Monkhorst-Pack mesh with 3 × 3 × 3 k-points. The geometry optimization was performed by considering the convergence criteria: the total energy, the forces acting on the atoms, the maximum stress, and the atomic displacement were 1.0 × 10 -5 eV / atom, 0.03eV / A, 0.05GPa and 0.001A, with a maximum SCF cycle of 500.
[0070] Table 1 Crystal information of colorless block crystals prepared in Example 1
[0071]
[0072] R1=Σ||Fo|-|Fo|| / Σ|Fo|.wR2=[w(Fo 2 -Fc 2 ) 2 ] / [wFo 4 ] 1 / 2 R1
[0073] Table 2. Fractional atomic coordinates of N2H4Zn(HC3N3O3) (×10 4 ) and equivalent isotropic displacement parameter
[0074]
[0075]
[0076] U eq Defined as orthogonal U ij 1 / 3 of the tensor.
[0077] Table 3 Selected bond lengths of N2H4Zn(HC3N3O3)
[0078]
[0079] 1 -1 / 2+X,3 / 2-Y,-1 / 2+Z; 2 +X,1-Y,1 / 2+Z
[0080] Table 4 Selected bond angles of N2H4Zn(HC3N3O3) (°)
[0081]
[0082] 1+X,1-Y,1 / 2+Z; 2 -1 / 2+X,3 / 2-Y,-1 / 2+Z; 3 1 / 2+X,3 / 2-Y,1 / 2+Z; 4 +X,1-Y,-1 / 2+Z
[0083] Table 5 Calculation results
[0084]
[0085] Table 6 Birefringence of cyanurate and isocyanurate
[0086]
[0087]
[0088] Table 7 Phosphorescence lifetime of some known and present organozinc compounds
[0089]
[0090] Table 8 d after retaining a certain primitive 11 and Δn value
[0091]
[0092] Result analysis:
[0093] As shown in Table 1, the colorless block crystals prepared in Example 1, i.e., the semi-organic crystals N2H4Zn(HC3N3O3) provided by the present invention, belong to the monoclinic system and have a space group of Cc. N2H4Zn(HC3N3O3) has a tetrahedral structure with Zn as the center and an infinite anion chain ([Zn 2+ (HC3NH3O3) 2- ]∞)( Figure 1 b), [Zn 2+ (HC3NH3O3) 2- ]∞ is connected in a diamond-like topological three-dimensional (3D) framework, where the infinite anion chain is connected to the infinite cation chain ([Zn(N2H4)] 2+ ∞) interweaving( Figure 1 c), two [Zn(N2H4)] 2+ The angle between the infinite chain and the c-axis is 38°. 2+ (HC3NH3O3) 2- ]∞ and the angle between the b-axis and the surface is 41°. In this network, the Zn-Zn distance (composed of two (HC3N3O3) 2- Ring bridging) or (bridged by two [N2H4] molecules)( Figure 1 c). Each Zn1 atom is tetrahedrally coordinated with two different (HC3N3O3) 2- 6-MR(Zn1-N1 / 3 bond length from arrive ) and two [N2H4] molecules (Zn1-N4 / 5 bond length is arrive between), resulting in the formation of highly polarized [Zn(HC3NH3O3)2(N2H4)2] tetrahedrons ( Figure 1 d). The Zn-N bond ratio coordinated with the neutral hydrazine group is (HC3N3O3) 2- The ring coordination bonds are slightly longer, which is mainly due to the Zn 2+ and (HC3NH3O3) 2- The electrostatic attraction between Figure 1 d). Considering the bond valence and (BVS) calculation results and the coordination environment of the Zn atom, the H atom was added to the N2 through geometry optimization to obtain the hydrogen-isocyanuric anion group (HC3N3O3) -2 ( Figure 1 e). In (HC3N3O3) -2 The length of the CN bond in the group ranges from 1.357 (4) to In contrast, the CO bond range is slightly wider, from 1.225(4) to In addition, the N-N bond within the [N2H4] molecule is These bond distances are in good agreement with those reported.
[0094] In the network structure of the semi-organic crystal provided by the present invention, there are two π-conjugated delocalizations (HC3N3O3) with different orientations. 2- Group, two (HC3NH3O3) 2- The dihedral angle between the bases is 40.9°, while the angle between two [N2H4] molecules is 38°. The [Zn(HC3N3O3)2(N2H4)2] tetrahedron is highly polarized, building a diamond-like 3D network ( Figure 1 f). Since there is no inversion center in the polar Cc space group, all polarized [Zn(HC3N3O3)2(N2H4)2] groups are uniformly arranged, which is conducive to the effective superposition of significant anisotropy and the second nonlinear susceptibility.
[0095] The infrared spectrum, ultraviolet visible spectrum and photoluminescence spectrum of the present invention show the optical properties of N2H4Zn(HC3N3O3). -1 1400-1700cm -1 The vibration at (HC3N3O3) 2- , 1157cm-1 and 1374cm -1 The vibrations at and are attributed to CO and CN, respectively. These are typical spectral features of cyanurate and isocyanurate derivatives. The UV-visible spectrum shows a cutoff edge at 217 nm (i.e., Eg = 5.38 eV), which is the shortest in the hydroxy isocyanurate family ( Figure 2 a).
[0096] The birefringence measurement experiment of the present invention uses a polarized optical microscope equipped with a Berek compensator and illuminated with a 589nm monochromatic green light source to measure the birefringence (Δn) characteristics of N2H4Zn (HC3N3O3) on the resulting crystal with a thickness of 4.71μm. Under the promotion of optical compensation, the extinction process produces a delay value of -1387.3nm, and the experimental value Δ nobv =0.294. Compared with the theoretical calculated value Δ ncal =0.306@589nm is consistent with ( Figure 2 b), which is larger than some other known cyanurates and isocyanurates, Pb2Cd(HC3N3O3)2(OH)2 (0.291@800nm), LiRbHC3N3O3·2H2O (0.259@532nm) and NaRb 0.84 Cs 0.16 HC3N3O3·2H2O(0.238@532nm). The large birefringence of N2H4Zn(HC3N3O3) may be mainly due to (HC3NH3O3) 2- This is caused by the strong anisotropy of the ring and the π-π conjugated interaction.
[0097] The present invention measures the particle size-dependent SHG response using the Kurtz Perry powder method under a 1064 nm laser with KDP as a reference. The SHG response of the N2H4Zn(HC3N3O3) sample increases with increasing particle size and reaches a plateau at about 180 μm, indicating that the sample can achieve phase matching ( Figure 2 c), and the maximum SHG response is 13 times that of KDP, and is the strongest among cyanurates. ( Figure 2 d).
[0098] The unique topological diamond-like framework of the semi-organic crystal N2H4Zn(HC3N3O3) provided by the present invention exhibits high thermal stability and strong water resistance. The present invention has studied its thermal stability, water resistance and air resistance. Unlike many isocyanurates, N2H4Zn(HC3N3O3) has an anhydrous 3D network structure, is thermally stable before 250°C, and will not decompose. In addition, after six months of exposure to ambient air and humidity, the crystals remain unaffected, with no degradation or hygroscopicity. Figure 3As shown in the figure, after immersion in water for 10 days, the N2H4Zn(HC3N3O3) crystals have basically not changed, and their XRD patterns have not changed before and after immersion. This water treatment does not affect the emission of green SHG light (532nm) ( Figure 3 ).
[0099] The phosphorescence experiment of the present invention tests the photoluminescence properties of the semi-organic crystalline material N2H4Zn (HC3N3O3) at room temperature. The excitation wavelength of the material is 310nm, the fluorescence emission band is relatively wide, and the peak value is about 360nm. The phosphorescence spectrum of the material ( Figure 4 c) shows that the emission peak position undergoes a dynamic red shift when the excitation wavelength is gradually changed from 290 nm to 410 nm. This shift is observed to transition from approximately 460 nm to a range between 460 and 565 nm, which indicates emission tunability. Figure 4 The material's dual-color emission capability was demonstrated: the emission peak at an excitation wavelength of 310 nm was located near 460 nm, which was blue light; the emission peak was red-shifted to about 500 nm, which was green light, when the excitation wavelength was 365 nm. The chromaticity diagram of the International Commission on Radiation (CIE) in 1931 confirmed this luminescence phenomenon ( Figure 4 d). About 1.2 seconds after the sample was exposed to light, continuous blue and green phosphorescence can be clearly observed with the naked eye ( Figure 5 d). Luminescence attenuation curve ( Figure 5 a and Figure 5 b) The multi-exponential decay behavior is further elucidated. For excitation wavelengths of 310 nm and 365 nm, the phosphorescence lifetimes are measured at 448 ms and 428 ms, respectively, with an average lifetime of more than 400 ms. This lifetime is superior to that of most zinc-based organic complexes ( Figure 5 c).
[0100] In order to clarify the relationship between the structure and properties of N2H4Zn(HC3N3O3), the first principle calculations were performed using the CASTEP software package. The electronic band structure shows that the valence band maximum (VBM) is located at point A and the conduction band minimum (CBM) is located at point M, and a direct band gap of 4.55 eV is calculated. Considering the trend of the band gap being underestimated due to the discontinuity of the exchange-correlation energy function, a 0.83 eV shear operator was used for subsequent optical property calculations. The total density of states and partial density of states (DOS) show that the band gap is mainly caused by the interaction between the C-2p and O-2p orbitals and the [HC3N3O3] 2- The energy bands associated with the Zn-4s, 3d, and 3p states, as well as the N-2p state in the [N2H4] group, are mainly located in the low energy region of -10 to -5 eV, with the smallest contribution near the Fermi level. The electron distribution curves of VBM and CBM ( Figure 6a, 6d) show that the VBM is mainly composed of On state, while the CBM is mainly derived from (HC3N3O3) 2- -π* state. Therefore, the organic component (HC3N3O3) 2- By promoting n-π* hopping to contribute to both CBM and VBM, this can effectively promote intersystem crossing (ISC) according to the EI-Sayed rule, favoring ultralong room-temperature phosphorescence, which is consistent with the proposed organic emission mechanism.
[0101] Previous studies have shown that when the bridging N atoms coordinate with H or Zn atoms, the band structure of the N-2p orbital in cyanuric acid 6-MR will shift down, resulting in an increase in the band gap of Zn(H2C3N3O3)2·3H2O. In the case of the title N2H4Zn(HC3N3O3) compound, one of the bridging N atoms forms an NH bond, while the other two bridging N atoms coordinate with two different Zn atoms to form Zn-N bonds. This arrangement effectively reduces the N-2p electronic state near the Fermi level, resulting in a band gap of 5.38 eV.
[0102] Refractive index calculations reveal different n z -n y <n y -n x The relationship shows that N2H4Zn(HC3N3O3) is a negative biaxial crystal. The calculated birefringence at 589nm is 0.306, which is consistent with the theoretical value of 0.294. Real space atomic cutting calculations show that (HC3N3O3) 2- The anionic groups mainly contribute to the optical anisotropy, which is 0.340 at 589nm. 2+ and N2H4 at 589nm are 0.079 and 0.049 respectively.
[0103] Using the Kleinman approximation of point group m, N2H4Zn(HC3N3O3) has a set of five non-zero SHG tensors, calculated to be d 12 =-7.6815pm·V -1 , d 13 =-1.652pm·L -1 , d 25 =-1.153pm·V -1 , d 36 =0.12pm·V -1 and d 11 =8.017pm·V -1 . Dominant d 11 Tensor ratio KDP d 36 The enhancement is about 20 times. 11SHG-weighted electron density analysis of the tensor was performed to quantify the contribution of each structural building block ( Figure 6 ). Unoccupied Virtual Electron (VE) Process ( Figure 6 b) and virtual hole (VH) ( Figure 6 c) The process shows that SHG mainly comes from (HC3N3O3) 2- Ring, Zn 2+ The contributions of N2H4 and N2H4 are not negligible, accounting for 79.60%, 10.50%, and 9.90%, respectively. This finding emphasizes the effective enhancement of the SHG effect in N2H4Zn(HC3N3O3) through the synergistic effect of multiple chromophores.
[0104] In summary, the SHG activity of the semi-organic crystalline N2H4Zn(HC3N3O3) prepared in Example 1 is more than 13 times that of KDP, and it has an abnormally long room temperature phosphorescence lifetime (448ms), and exhibits visible and tunable blue and green afterglow for up to 1.2 seconds.
[0105] The foregoing is merely a specific embodiment of the present invention, which enables those skilled in the art to understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features claimed herein.
Claims
1. A semi-organic crystalline material, characterized in that: The chemical formula of the semi-organic crystal is N2H4Zn(HC3N3O3), where HC3N3O3 represents cyanuric acid. 2- ; The semi-organic crystal belongs to the monoclinic system, and the space group is Cc The unit cell parameters of the semi-organic crystal are: a = 9.4696(5)Å, b = 9.4104(4)Å, c = 7.9944(4)Å, α = 90°, β =113.333(2)°, γ = 90°, unit cell volume V = 645.46(3) Å 3 ; From the c-axis direction, the semi-organic crystal has a tetrahedral structure centered on Zn; the semi-organic crystal has two [Zn(N2H4)] 2+ ∞) infinite chain and two [Zn 2+ (HC3N3O3) 2- ]∞ infinite chain, viewed from the c-axis direction, two [Zn(N2H4)] 2+ ∞) infinite chain and two [Zn 2+ (HC3N3O3) 2- ]∞Infinite chains are connected to form a diamond-like topological three-dimensional structure.
2. A method for preparing the semi-organic crystalline material according to claim 1, characterized in that: A semi-organic crystalline material is obtained by hydrothermal reaction of CH6N4·HNO3, ZnBr2 and C3H3N3O3; Among them: CH6N4·HNO3 represents aminoguanidine nitrate, and C3H3N3O3 represents melamine.
3. The method for preparing a semi-organic crystalline material according to claim 2, characterized in that: The semi-organic crystalline material is obtained by hydrothermally reacting CH6N4·HNO3, ZnBr2 and C3H3N3O3, including: The semi-organic crystalline material is obtained by keeping CH6N4·HNO3, ZnBr2 and C3H3N3O3 in a molar ratio of 1:1:1 in water at 120-160°C for 2-7 days and cooling to room temperature within 1-5 days.
4. Use of the semi-organic crystalline material according to claim 1 in any field of optical computing, optical switching, long-distance communication, information encryption and anti-counterfeiting, biological imaging, lighting, and long afterglow devices.
5. A nonlinear optical device, characterized in that: A nonlinear optical device is constructed using the semi-organic crystalline material according to claim 1.
6. A nonlinear optical device, characterized in that: Comprising the nonlinear optical device as claimed in claim 5.
Citation Information
Patent Citations
IIB metal organic complex fluorescent light-emitting material
CN101993690A